Teologi Komparatif bagi Tradisi Reformed di Indonesia: Sebuah Proposal - Lefrandy Praditya (STT Reformed Injili Internasional, 2022)
The Reformed theologian, Benyamin Fleming Intan, analyzed Christian theologians thinking in Indonesia and found out that Pancasila did not contradict with Christianity. In line with this, when the young Reformed theologian, Nathaniel Gray Sutanto assessed the relationship between Pancasila and Christianity. then he provided an epistemological framework that the existence of the Indonesian state and Pancasila had been allowed by sovereign of God. Based on their epistemological framework, I want to go over them by offering a new and more concrete way or approach in multireligious context, called comparative theology. For this reason, the author examines definition and development of comparative theology with the latest comparative theology books, then, the author also looks into the Bible and church history. That comparative theology has been carried out by biblical writers and figures in the church history even though theology comparative has not become a scientific discipline yet. I argue that comparative theology can be used in Indonesia with Reformed tradition because the nature of comparative theology is hospitable for religious harmony and still being faithful to the Bible testimony.